The "Big Five" personality traits of presidents and the relaxation of term limits in Latin America. Issue 1 (2nd January 2022) - Arana Araya, Ignacio
ABSTRACT: Thirty-one presidents from every Latin American country – excluding Mexico – who were governing from 1945 to 2012 tried forty times to change the constitution of their countries to overstay in office. These attempts often caused severe political instability. Current explanations of the variability of term limits have centred on the context in which presidents govern despite the protagonism of the leaders in the constitutional changes. I argue that the personality traits of presidents are an important driver of their overreaching behaviour. Centred on the paradigm of the "Big Five, " I propose hypotheses about a causal relationship between each of the five core personality factors – openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism – and the presidents' attempts to alter their term limits. To test the theory, I use data about presidents who governed from 1945 to 2012. The results of a discrete-time duration analysis show that three of the Big Five are associated to the likelihood of observing a president changing term limits. I conclude by discussing how this research agenda should be extended to uncover how the uniqueness of the leaders explains relevant outcomes in executive politics.